Neuropeptide Receptor Ligands for the Treatment of Schizophrenia: Focus on Neurotensin and Tachykinins - Griebel, Guy (Current Pharmaceutical Design, 2015)
There is a wealth of evidence that various neuropeptides and their receptor ligands modulate schizophrenia- related behaviors in preclinical animal models, suggesting that neuropeptide systems may represent potential novel therapeutic targets for the treatment of schizophrenia. In particular, neurotensin and tachykinins have been the subject of significant research efforts, generating compelling preclinical data in the schizophrenia field. However, clinical studies with notably selective tachykinin NK3 receptor antagonists in schizophrenia have been disappointing, and they were unable to confirm the promising therapeutic potential from animal studies, thereby questioning the therapeutic utility of these compounds for this condition. This article reviews preclinical and clinical findings on ligands for neurotensin and tachykinin receptors in schizophrenia, and provides possible explanations for the failure so far to develop small-molecule neuropeptide ligands for the treatment of schizophrenia.
Keywords: Schizophrenia